Damage of shotcrete under freeze-thaw loading - Chen, Jianxun; Zhao, Pengyu; Luo, Yanbin; Deng, Xianghui; Liu, Qin (Journal of Civil Engineering and Management, 2017)
The freeze-thaw durability of shotcrete can be improved by adding an air-entraining agent in cold areas. The main focus of this paper is to investigate the changes in the internal pore structure of C25 ordinary shotcrete and shotcrete mixed with a RM-YQ air-entraining agent using computed tomography (CT) scanning technique during freeze-thaw cycles. The macroscopic tests were conducted, including mass loss, dynamic modulus of elasticity and ultrasonic wave velocity tests. Results were compared, and the freeze-thaw durability characteristics of shotcrete mixed with the air-entraining agent were revealed. Adding an air-entraining agent could reduce the number of pores largely that ranged mainly from 0.01 mm2 to 1.00 mm2 (excluding the pores or bubbles < 0.01 mm2 because of the precision of the CT scanning system), and could therefore improve the initial pore structure of the formed shotcrete. During first few freeze-thaw cycles, just few small pores formed. After cement mortar fragmentations appeared, the number of small pores (0.01 mm2 to 0.50 mm2) in ordinary shotcrete increased significantly. The pore structure deteriorated largely. However, this could be prevented effectively by adding an air-entraining agent. Therefore, the freeze–thaw durability of shotcrete was improved.